APPLICATIONS SOFTWARE FOR PC CLONNING BETWIN - Irvin Oktareza YR; Fivtatianti, H., SKom., MM Fivtatianti, H., SKom., MM (Jurnal Sistem Komputer, 2004)
Writing about one way of describing the importance of addressing the current needs of the computer on which it takes lots of computer equipment needed along with the large number of computers required. And seeks to maximize the computer device so that the costs required to purchase computer equipment that is not a lot of ability is good enough. In addition to cost savings role in the author also emphasizes ease of installation process. All the above can be overcome with the use of software for PC Clonning Betwin.Betwin itself is easy to use software because it can be understood and used easily and can run on Windows operating systems.